Correlations between molecular structure and biological activity in "logical series" of dietary chromone derivatives - Lewandowski, Włodzimierz (PLoS One, 2020)
The research was conducted in the “logical series” of seven ligands: chromone, flavone, 3-hydroxyflavone, 3,7-dihydroxyflavone, galangin, kaempferol and quercetin. Each subsequent ligand differs from the previous one, among others by an additional hydroxyl group. The studied chromone derivatives are plant secondary metabolites which play an important role in growth, reproduction, and resistance to pathogens. They are important food ingredients with valuable pro-health properties. The studies of the relationships between their molecular structure and biological activity facilitate searching for new chemical compounds with important biological properties not by trial and error, but concerning the impact of specific changes in their structure on the compound properties. Therefore several pectroscopic methods (FT-IR, FT-Raman, (1)H and (13)C NMR) were applied to study the molecular structure of the compounds in the series. Moreover the quantum-chemical calculations at B3LYP/6-311++G** were performed to obtained the theoretical NMR spectra, NBO atomic charge, global reactivity descriptors and thermodynamic parameters. The antioxidant activity of the compounds was tested in the DPPH and FRAP assays and the mechanism of antioxidant activity was discussed based on the results on theoretical calculations. The cytotoxicity of the ligands toward human epithelial colorectal adenocarcinoma Caco2 cells was estimated and correlated with the lipophilicity of the compounds. The principal component analyses (PCA) and hierarchical cluster analysis were used to study the dependency between the molecular structure of ligands and their biological activity. The experimental data were related to the theoretical ones. The found regular changes in physicochemical properties correlated well with the systematic changes in antioxidant and biological properties.